Paediatric acute respiratory distress syndrome: consider the role of lymphatics. Issue 7 (27th July 2022) - Lu, Mimi; Cavazzoni, Elena; Selvadurai, Hiran; Burren, Juerg Martin
Abstract : We present a case of a 7-day-old male infant with severe respiratory disease requiring venoarterial extracorporeal membrane oxygenation therapy with evidence of lymphangiectasia on lung biopsy. Differentiating primary versus secondary lymphangiectasis in this patient remains a riddle despite extensive investigations including an infective screen, lung biopsy and whole-genome sequencing. In addition to the standard therapies used in paediatric acute respiratory distress syndrome, such as lung-protective ventilation, permissive hypoxaemia and hypercarbia, nursing in the prone position, early use of muscle relaxants, rescue intravenous corticosteroids and broad-spectrum antibiotics, the patient was also given octreotide despite the absence of a chylothorax based on the theoretical benefit of altering the lymphatic flow. His case raises an interesting discussion around the role of lymphatics in the pathophysiology of paediatric and adult respiratory distress syndrome and prompts the exploration of novel agents which may affect lymphatic vessels used as an adjunctive therapy.